2022
DOI: 10.3389/fgene.2022.952667
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress for RNA Modifications in Physiological and Pathological Angiogenesis

Abstract: As a critical layer of epigenetics, RNA modifications demonstrate various molecular functions and participate in numerous biological processes. RNA modifications have been shown to be essential for embryogenesis and stem cell fate. As high-throughput sequencing and antibody technologies advanced by leaps and bounds, the association of RNA modifications with multiple human diseases sparked research enthusiasm; in addition, aberrant RNA modification leads to tumor angiogenesis by regulating angiogenesis-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 161 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Anti-angiogenic therapy is an important modality for digestive system tumor treatment ( 122 ). Due to the low mutation rate of anti-angiogenic genes in CRC ( 122 ), epigenetic modifications may provide a more appropriate target for blocking tumor angiogenesis. The role of m6A regulation in tumor angiogenesis is currently a topic of intense research.…”
Section: Potential Research Direction For Mettl14 and Digestive Syste...mentioning
confidence: 99%
“…Anti-angiogenic therapy is an important modality for digestive system tumor treatment ( 122 ). Due to the low mutation rate of anti-angiogenic genes in CRC ( 122 ), epigenetic modifications may provide a more appropriate target for blocking tumor angiogenesis. The role of m6A regulation in tumor angiogenesis is currently a topic of intense research.…”
Section: Potential Research Direction For Mettl14 and Digestive Syste...mentioning
confidence: 99%
“…In the present study, we first screened 29 m7G regulators differentially expressed in osteosarcoma and found them abundant in biological functions such as initiation and regulation of translation and RNA catabolic processes by enrichment analysis. In fact, m7G methylation, as a critical component of post-transcriptional modification, is involved in various aspects of cancer RNA metabolism that have been extensively characterized, including miRNA maturation, mRNA translation, and mRNA decay [22] , [67] , [68] . In hepatocellular carcinoma, METTL1-mediated m7G tRNA modification enhanced mRNA translation in a codon frequency-dependent manner and accelerated tumorigenesis and progression in vitro and in vivo [20] .…”
Section: Discussionmentioning
confidence: 99%
“…5-Methylcytosine (m 5 C) methylation was considered an mRNA modification approach first reported in 1925 [ 12 – 14 ]. As recognized by previous studies, this RNA modification is also regulated by writers, readers, and erasers and plays an important role in biological progression by influencing RNA stability, transcription efficiency, and localization [ 15 17 ]. Reportedly, m 5 C can affect tumor progression, prognosis, and TIME as well as resistance to immunotherapy and chemotherapy [ 15 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this kind of lncRNA is also considered a promising biomarker and potential target for tumor diagnosis and may provide a novel strategy to guide individualized precise treatment for tumor patients. Increasing evidence-based studies have determined that m 5 C can regulate related lncRNAs to participate and influence biological processes [ 15 17 , 22 ]. Previous studies have shown that NSUN2 can alter gene and lncRNA expression as well as enhance protein synthesis and translation [ 14 , 23 ].…”
Section: Introductionmentioning
confidence: 99%